A Conjugated Polymer Containing Arylazopyrazole Units in the Side Chains for Field‐Effect Transistors Optically Tunable by Near Infra‐Red Light. Issue 33 (5th June 2020) - Tian, Jianwu; Liu, Zitong; Jiang, Wenlin; Shi, Dandan; Chen, Liangliang; Zhang, Xisha; Zhang, Guanxin; Di, Chong‐an; Zhang, Deqing
Abstract: Optically tunable field‐effect transistors (FETs) with near infra‐red (NIR) light show promising applications in various areas. Now, arylazopyrazole groups are incorporated in the side chains of a semiconducting donor–acceptor (D‐A) polymer. The cis–trans interconversion of the arylazopyrazole can be controlled by 980 nm and 808 nm NIR light irradiation, by utilizing NaYF4 :Yb, Tm upconversion nanoparticles and the photothermal effect of conjugated D‐A polymers, respectively. This reversible transformation affects the interchain packing of the polymer thin film, which in turn reversibly tunes the semiconducting properties of the FETs by the successive 980 nm and 808 nm light irradiation. The resultant FETs display fast response to NIR light, good resistance to photofatigue, and stability in storage for up to 120 days. These unique features will be useful in future memory and bioelectronic wearable devices. Abstract : Field‐effect transistors (FETs) tunable by near‐IR light with conjugated polymers incorporating arylazopyrazole groups in the side chains are reported and investigated. These FETs have great potential in new memory and bioelectronic wearable devices, demonstrating a fast response, good resistance to photofatigue, and stable storage for up to 120 days.